Strategi Komunikasi Forum Kerukunan Umat Beragama dalam Meningkatkan Toleransi dan Kebebasan Beragama di Kabupaten Garut - Farhan Mubarok; Ummu Salamah; Feri Purnama (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The diversity of religious life is truly very interesting, because this diversity provides inner and outer peace. Tolerance also essentially refers to human attitudes or behavior that adhere to rules, allowing individuals to evaluate and respect the actions of others. This research uses a qualitative descriptive method with the main focus on uncovering the communication strategies used by the FKUB (Religious Harmony Forum) in Garut Regency to encourage tolerance and religious freedom based on communication strategy theory (Arifin, 1984). Dynamics of inter-religious harmony in Garut Regency after the issuance of Regional Regulation Number 14 of 2022 concerning the Implementation of Tolerance in Community Life. Providing a significant impact on well-coordinated collaborative efforts in preventing and resolving intolerance or conflict in the Garut region. The facts on the ground are that there have been no incidents of intolerance reported in Garut over the last two years.